2017
DOI: 10.1007/s12639-017-0925-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Sarcocystis species in raw hamburgers using PCR–RFLP method in Kashan, central Iran

Abstract: The prevalence of bovine is high in the most regions of the world. It can be a human health problem due to consumption of raw or under cooked hamburgers or other bovine meat products. This study was carried out to investigate the prevalence and species identification of among of hamburgers, using PCR-RFLP methods in Kashan, central Iran. Overall 200 raw industrial hamburgers samples with at least 60% meat were randomly collected from nine different brands in Kashan, central Iran. The genomic DNA was extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
2
18
1
Order By: Relevance
“…The prevalence of S. hominis infection in different countries based on molecular methods is poorly studied. A 0.2% prevalence of S. hominis was detected in China [50], 0.5% in Argentina [42], 3.5% in Iran [44], 6.2 % in Germany [37] and 12.5% in the Netherlands [10]. The molecular technique established in this study is an important step in the development of zoonotic S. hominis diagnosis in both cattle and humans.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…The prevalence of S. hominis infection in different countries based on molecular methods is poorly studied. A 0.2% prevalence of S. hominis was detected in China [50], 0.5% in Argentina [42], 3.5% in Iran [44], 6.2 % in Germany [37] and 12.5% in the Netherlands [10]. The molecular technique established in this study is an important step in the development of zoonotic S. hominis diagnosis in both cattle and humans.…”
Section: Discussionmentioning
confidence: 72%
“…Nevertheless, several trends in the prevalence of Sarcocystis species can be indicated. Most studies carried out in cattle reported the highest prevalence of S. cruzi employing canids as definitive hosts [10,14,15,18,37,[40][41][42][43][44]. By contrast, a relatively low prevalence of S. hirsuta using felids as definitive hosts was often recorded [14,15,37,41,45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations